FLOUTING MAXIM IN HARRY POTTER AND THE ORDER OF THE PHOENIX MOVIE - Ayu Dhika Permata Putri (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This research aims to identify the types of flouting maxim in Harry Potter and the Order of the Phoenix movie. A movie is one of the most popular forms of entertainment that allows people to enter an imaginary world without actually experiencing it. Therefore, a movie is frequently used as the data source for research since it reflects people's daily life. The character's utterance in the movie might occasionally contain additional meaning, hence it is very important to recognize in order to avoid misinterpretation. To assist in conducting the research, theory from Grice (1975) was used as guidelines. The Movie is downloaded from the internet and the data were collected in the form of characters’ utterances throughout the movie. The descriptive qualitative method was used to analyze the data by narratively describing the data that belong to one of the flouting maxim types. As a result, it is found that the characters flouted all types of maxim and the occurrences are 35 times throughout the movie.